2020
DOI: 10.1186/s12889-020-09919-4
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use patterns and chronic health conditions among people experiencing homelessness in MN: a statewide survey

Abstract: Background Adults experiencing homelessness have higher rates of disease and premature morbidity compared to the general population. Tobacco use is a primary contributing factor to these disparities; however, less is known regarding e-cigarette use patterns among adults experiencing homelessness and whether e-cigarettes are used in a manner that is narrowing or widening health disparities. This study aimed to describe the 1) prevalence and trends in e-cigarette use, 2) correlates of e-cigarette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Dual use, which is the most common usage pattern, is riskier than using either product alone [ 87 ]. Dual use, with even passive exposure to EC, was identified as significant predictor for asthma in two more cross-sectional studies [ 73 , 92 ] and one meta-analysis [ 93 ]. A recently published systematic review concluded that evidence up to now suggests that the side effects of ECs may be exaggerated in people with asthma [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dual use, which is the most common usage pattern, is riskier than using either product alone [ 87 ]. Dual use, with even passive exposure to EC, was identified as significant predictor for asthma in two more cross-sectional studies [ 73 , 92 ] and one meta-analysis [ 93 ]. A recently published systematic review concluded that evidence up to now suggests that the side effects of ECs may be exaggerated in people with asthma [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adolescents with asthma were more likely to be dependent on nicotine compared to their non-asthmatic counterparts [ 115 , 116 ]; they started smoking earlier because of curiosity about cigarettes and continued because it improved their stress and anxiety [ 116 ]. There is strong evidence that bad mental health is associated with EC in asthmatics as well as with tobacco cigarette and illicit substance use [ 92 , 96 , 110 ]. This population was at increased risk of dual use of conventional cigarettes and EC and those who used ECs presented higher tobacco cigarette smoking susceptibility [ 85 , 90 , 103 , 115 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in multivariate analysis, controlling for all other relevant variables, a higher number of hospital admissions was found among current smokers, participants with lower level of physical and mental health-related quality of life, and self-reported binge drinking. It is established that cigarette smoking exacerbates the severity of chronic illnesses and impairs successful symptoms management [72][73][74]. Knowing that racial and ethnic minority middle-aged and older adults are at greater risk for chronic disease morbidity than their non-Latino White counterparts, effective interventional studies must target racial and ethnic minority older smokers with co-morbidities [75].…”
Section: Need-for-care Characteristics and Healthcare Utilizationmentioning
confidence: 99%
“…As the landscape of available tobacco products has evolved to include alternative tobacco and nicotine products, the patterns of tobacco use have also changed among PEH. Two-thirds of current smokers who experience homelessness report the use of alternative tobacco products, including blunts and cigarillos (little cigars) or electronic nicotine delivery systems, with e-cigarettes being the most common form [ 6 , 7 , 8 , 9 ]. The concurrent use of these products and cigarette smoking might suggest increased nicotine dependence; however, few studies have explored this among PEH.…”
Section: Introductionmentioning
confidence: 99%